Developmental nonlinearity drives phenotypic robustness - Rebecca M. Green (Nature Portfolio, 2017)
Developmental processes often involve nonlinearities, but the consequences for translating genotype to phenotype are not well characterized. Here, Green et al. vary Fgf8 signaling across allelic series of mice and show that phenotypic robustness in craniofacial shape is explained by a nonlinear effect of Fgf8 expression.